2017
DOI: 10.12697/fce.2017.54.16
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of epiphytic lichens and bryophytes on aspen (Populus tremula) in the middle boreal forests of Republic of Karelia (Russia)

Abstract: Abstract:The distribution of epiphytic bryophyte and lichen species growing on aspen in the middle boreal forests was studied in southern Karelia (Russia). These forests varied in time-since-disturbance from 80 to 450 years. (2007) were found. Relationships between epiphytic lichen and bryophyte species richness and certain environmental variables (at different trunk heights above ground and time-since-disturbance) were evaluated. Lichens and mosses on aspen trunks often occupy different ecological niches. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
17
1
2
Order By: Relevance
“…-Frequent. 1: spruce forest, on the soil (Boichuk et al, 2002); 3: spruce forest, on the ground, collected more than 10 times (INEP 205 (Boichuk et al, 2002, KPABG 109196); 3: old-growth spruce forest, on fallen pine and spruce trunks, collected more than 10 times (INEP 133); 6: mixed aspen-spruce forest at an aspen trunk base (Tarasova et al, 2017 2: swampy spruce forest, waterlogged site (Boichuk et al, 2002, KPABG 108838). harpanthus flotovianus (Nees) Nees -Unique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Frequent. 1: spruce forest, on the soil (Boichuk et al, 2002); 3: spruce forest, on the ground, collected more than 10 times (INEP 205 (Boichuk et al, 2002, KPABG 109196); 3: old-growth spruce forest, on fallen pine and spruce trunks, collected more than 10 times (INEP 133); 6: mixed aspen-spruce forest at an aspen trunk base (Tarasova et al, 2017 2: swampy spruce forest, waterlogged site (Boichuk et al, 2002, KPABG 108838). harpanthus flotovianus (Nees) Nees -Unique.…”
Section: Resultsmentioning
confidence: 99%
“…The first list of bryophytes of the National Park (Karelian part only) was published in 2002 (Boi-chuk et al, 2002) and included 24 liverworts and 161 mosses. Four species (Liochlaena lanceolata, Lophocolea heterophylla, Lophozia guttulata, and Plagiochila porelloides) were listed as newly observed in the National Park in a study of epiphytic lichens and bryophytes on aspen (Populus tremula) in Karelia (Tarasova et al, 2017). Two red-listed liverwort species (Syzygiella autumnalis and Scapania apiculata) from the National Park were found later (Borovichev et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, for biodiversity of boreal forest, aspen is supposed to be a hotspot in both Eurasia and North America (Lundström et al, 2013). In our previous lichen inventory of forest communities in middle boreal subzone of Karelia (Tarasova et al, 2017), 178 species were found on aspen trees. The 83 lichens were common on both as-pen and spruce according to a comprehensive analysis of species composition on both trees.…”
Section: List Of Speciesmentioning
confidence: 95%
“…Sample plots were located in the Karelian part of the Vodlozero National Park (62°13'N, 36°46'E; 130,600 ha), Kivach Strict Nature Reserve (62°17'N, 34°00'E; 10,880 ha), Kizhi Sanctuary (62°06'N, 35°09'E; 50,000 ha) and Petrozavodsk City (61°50'N, 34°20'E; 13,500 ha). The location of these study areas was mapped and their climatic characteristics presented in a previous paper (Tarasova et al, 2017). Vodlinsky forest (62°06'N, 37°44'E; 142,630 ha) is located in the Pudozh district, bordering to the north and east with Arkhangelsk region, and to the west, with Vodlozero National Park.…”
Section: Study Areamentioning
confidence: 99%
“…Se conoce en el oeste de Norteamérica, Europa central y septentrional y Siberia (Santesson et al, 2004;Boom & Palice, 2006;Liška et al, 2008;Spribille et al, 2008;Zhdanov, 2010;Tarasova et al, 2017;Nimis et al, 2018). Extremadamente rara en toda su área de distribución, ha sido clasificada como "Vulnerable" en las Islas Británicas (Woods & Coppins, 2012).…”
Section: Candelariella Commutataunclassified